THE INFLUENCE OF CELEBRITY ENDORSEMENT AND CUSTOMER REVIEWS ON PURCHASING DECISIONS FOR SAMSUNG SMARTPHONES IN SIDOARJO DISTRICT - Nuzulul Kiromi, Mukhamad (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2025)
This study aims to determine the effect of celebrity endorsement and customer reviews on purchasing decisions for Samsung brand smartphones in Sidoarjo Regency. In the current era of digitalization, marketing strategies do not only rely on product features, but are also influenced by celebrity endorsements and customer reviews that are widespread through social media and digital platforms. This research uses a quantitative approach. The population in this study were Samsung smartphone consumers in Sidoarjo Regency, with a sample size of 150 respondents obtained through accidental sampling technique. Data collection was carried out by distributing questionnaires, and data analysis using multiple linear regression with the help of SPSS software version 26. The results showed that both celebrity endorsement and customer review had a positive and significant effect partially on purchasing decisions. Simultaneously, the two variables also have a significant effect on purchasing decisions. These findings indicate that celebrity endorsement and customer review-based marketing strategies can be effective tools in shaping preferences and increasing consumer purchasing decisions for certain brands